2020
DOI: 10.1111/crj.13161
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragm thickening assessed by ultrasonography is lower than healthy adults in patients with chronic obstructive pulmonary disease

Abstract: Background Ultrasound imaging has been widely used for imaging of the diaphragm thickness (Tdi) and thickening. Few studies assessed the Tdi using ultrasonography in patients with chronic obstructive pulmonary disease (COPD). We measured the Tdi and thickening in patients with COPD compared with healthy younger and healthy older adults to reveal the influence of ageing and/or COPD. Methods Thirty‐eight male patients with COPD (age 72 ± 8 years), 15 healthy younger (age 22 ± 1 years) and 15 healthy older (age 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…DUS findings are well established in many previous studies. 10 , 11 , 16 Patients were placed in a supine position, and the tests were performed at the right hemidiaphragm. A linear ultrasound probe (5–12 MHz) was used to measure the thickness of the diaphragm (DT) by B-mode.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…DUS findings are well established in many previous studies. 10 , 11 , 16 Patients were placed in a supine position, and the tests were performed at the right hemidiaphragm. A linear ultrasound probe (5–12 MHz) was used to measure the thickness of the diaphragm (DT) by B-mode.…”
Section: Methodsmentioning
confidence: 99%
“…The thickening fraction of the diaphragm (TF) has been evaluated in many studies. 10 , 11 , 15 It is related to the generation of diaphragm muscle pressure. The TF was calculated with the DT value.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, many studies were conducted to evaluate the diaphragm thickness in patients with COPD using ultrasonography [5,8,9]. In one study, reduced diaphragm thickness compared to healthy adults was shown [5], which was considered as an indicator of diaphragm dysfunction, however, no difference was observed in another study [9]. Pulmonary rehabilitation (PR), a multicomponent intervention based on individually tailored exercise training, education, dietary advice, psychological and behavioral intervention has emerged as arguably the most effective non-pharmacological treatment in improving exercise capacity, dyspnea, and quality of life in patients with COPD 3 3 [10,11].…”
Section: Introductionmentioning
confidence: 99%